Girls’ Reluctance and Intersectional Identities in STEM-Rich Makerspaces - Priyanka Parekh (Education Sciences, 2024)
Craft and e-textile circuits are technologies that bridge the gender gap in Science, Technology, Engineering, and Mathematics (STEM) learning. Acknowledging the need to study girls’ underrepresentation in STEM, this article delves into the identity negotiations of four girls aged eleven to fourteen as they construct craft and e-textiles at a library makerspace. Qualitative analysis of their talk at the workshop found that several factors shaped the girls’ identity work, such as their awareness of their abilities and fellow participants’ projects, their understanding of parents’ expectations, and their strengths in other STEM domains. While all four girls reluctantly participated in making circuits, the reason for their reluctance varied from an interest in craft and the messiness of working with conductive thread to the preference for familiarity and complexity within other STEM domains such as programming and engineering. Further, as the girls questioned their need to engage in circuit-making, their preference for a particular identity became apparent. Overall, this study’s findings underscore the tensions in learning in technology-rich environments such as makerspaces, highlighting maker technologies’ affordances and limitations and emphasizing the need for a deeper understanding of what shapes learners’ participation and identities.